Laporan Laba Rugi Komprehensif - Elisabeth Da Rato; Wahidahwati Wahidahwati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of Writing this Paper To find out the definition, usefulness, limitations, elements, and formats on the comrehensive profit and loss statement. The income statement presents a measure of the successful performance achieved by the reporting entity in one current period. This report reflects the operating activities of the entity. The profit and loss statement provides details of the entity's earnings, expenses, profits and losses for a period of time. The accounting model that is still in use today is historical costs, where assets and liabiitas are assessed based on the price obtained at the time of the actual transaction in the past. The comprehensive profit and loss statement not only covers unaddressed gains or losses, but also covers realized gains or losses.